Smart Aquaponics Monitoring and Control System Using Internet of Things Technology - Endang Hendayatna (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2026)
Aquaponics is an integrated farming system that combines fish farming (aquaculture) with plant cultivation (hydroponics) in a mutually supportive environment. Aquaponics provides an attractive solution in terms of limited land use in urban areas. In its development, the use of Internet of Things (IoT) technology has made a significant contribution in increasing the efficiency and success of aquaponic systems. The method used in this study is to utilize sensors connected to the IoT network, such as ultrasonic and DHT22 sensors to collect data on important parameters in the aquaponic system, such as temperature and water level, and humidity. The sensor will provide information to the Arduino Uno microcontroller, then the microcontroller will order the water pumps, lights and fans to turn on or off. This system is also equipped with a user interface that allows users to monitor and control the aquaponic system in real-time via a mobile device.